the Use of Library Resources at the Nigerian Institute of Advanced Legal Studies by the Research Fellows for Improved Library Services - Hussaini , Ali; Owoeye , Jide Edward (MiddleBelt Journal of Library and Information Science, 2020)
This paper reported the findings of a study on the Nigerian nstitute of Advanced Legal Studies library use by the Institute Research Fellows. The main bjective of the study was to determine the extent to which the Research Fellows of the Institute utilize the resources of the Institute Library. The study adopted a descriptive survey method of research. The population of the study was 54 Research Fellows in the Institute. The sample size is 20 (number of Research Fellows in Lagos Office). The major tool of data collection was a self-developed questionnaire, which was distributed among the Research Fellows in the Lagos Office of the Nigerian Institute of Advanced Legal Studies. All the copies of the questionnaires distributed were retrieved. The findings of the study revealed that 30% of the Research Fellows visited the library often. Statutes were the most consulted resources (65%), followed by law reports and periodicals (60%). The most relevant of the resources consulted were also statutes (90%), followed by law reports (85%). Inadequate current materials and difficulty in accessing the Internet were the major obstacles for the use of the library. The paper recommended, mong others, acquisition and subscription to current print and electronic databases, increased bandwidth of the Institute wireless network, improved aesthetics of the library and installation of adequate and functional air conditioners in the library to facilitate the provision of more relevant information by the library.